Structural stabilities and electronic properties of Mn2ST2 monolayers (T=O, F, and Cl): a first-principles investigation - Anan Udomkijmongkol; Komsilp Kotmool (Physica Scripta, 2025)
Abstract The structural, energetic, and electronic properties of Mn 2 S monolayers and their functionalized derivatives were systematically investigated using first-principles calculations. The pristine Mn 2 S monolayers, existing in the 1T and 2H phases, exhibited metallic characteristics with intrinsic magnetism. However, phonon dispersion analysis reveals dynamic instability in both phases, indicating that pristine Mn 2 S is not a stable monolayer material. To enhance stability, we examined the effects of oxygen (O), fluorine (F), and chlorine (Cl) functionalization on Mn 2 S, constructing twelve distinct Mn 2 ST 2 configurations for each phase. The findings demonstrate that functionalization significantly alters the energetic hierarchy, with different configurations emerging as the most stable phase across all functional terminations. Phonon dispersion analysis confirms the dynamical stabilities of the 1T-Mn 2 SO 2 , 2H-Mn 2 SO 2 , 2H-Mn 2 SF 2 , and 1T-Mn 2 SCl 2 . Mulliken charge analysis further highlights significant charge redistribution upon functionalization, enhancing charge localization and stability. Among the various Mn 2 ST 2 structures, functionalization plays a crucial role in stabilizing the monolayers. The 1T and 2H phases of Mn 2 SO 2 are identified as the most energetically and dynamically stable configurations, characterized by strong Mn-O bonding and a ferromagnetic half-metallic ground state. In contrast, the most stable form of Mn 2 SF 2 adopts a 2H phase, exhibiting antiferromagnetic ordering and a band gap of 1.617 eV. Additionally, a stabilized 1T-Mn 2 SCl 2 demonstrates ferromagnetic behavior and functions as a ferromagnetic semiconductor with a narrow band gap of 0.196 eV. These findings highlight the critical role of surface functionalization in stabilizing Mn 2 S monolayers and tailoring their electronic and magnetic properties, paving the way for potential applications in spintronics and nanoelectronics.
Keywords: 2D Materials and Applications; MXene and MAX Phase Materials; Heusler alloys: electronic and magnetic properties